Biodistribution of P-selectin targeted microbubbles. (June 2014) - Warram, Jason M.; Sorace, Anna G.; Mahoney, Marshall; Samuel, Sharon; Harbin, Bryant; Joshi, Madhura; Martin, Amber; Whitworth, Lee; Hoyt, Kenneth; Zinn, Kurt R.
Abstract Purpose: To evaluate binding of P-selectin targeted microbubbles (MB) in tumor vasculature; a whole-body imaging and biodistribution study was performed in a tumor bearing mouse model. Methods: Antibodies were radiolabeled with Tc-99 m using the HYNIC method. Tc-99 m labeled anti-P-selectin antibodies were avidin-bound to lipid-shelled, perfluorocarbon gas-filled MB and intravenously injected into mice bearing MDA-MB-231 breast tumors. Whole-body biodistribution was performed at 5 min (n = 12) and 60 min (n = 4) using a gamma counter. Tc-99 m-labeled IgG bound IgG-control-MB group (n = 12 at 5 min; n = 4 at 60 min), Tc-99 m-labeled IgG-control-Ab group (n = 5 at 5 min; n = 3 at 60 min) and Tc-99 m-labeled anti P-selectin-Ab group (n = 5 at 5 min; n = 3 at 60 min) were also evaluated. Planar gamma camera imaging was also performed at each time point. Results: Targeted-MB retention in tumor (60 min: 1.8 ± 0.3% ID/g) was significantly greater (p = 0.01) than targeted-MB levels in adjacent skeletal muscle at both time points (5 min: 0.7 ± 0.2% ID/g; 60 min: 0.2 ± 0.1% ID/g) while there was no significant difference (p = 0.17) between muscle and tumor retention for the IgG-control-MB group at 5 min. Conclusions: P-selectin targeted MBs were significantly higher in tumor tissue, as compared with adjacent skeletal tissue or tumor retention of IgG-control-MB.